Combinatorial Strategies for Synthesis and Characterization of Alloy Microstructures over Large Compositional Ranges. - Li, Yanglin; Jensen, Katharine E; Liu, Yanhui; Liu, Jingbei; Gong, Pan; Scanley, B Ellen; Broadbridge, Christine C; Schroers, Jan (ACS combinatorial science, 2016)
The exploration of new alloys with desirable properties has been a long-standing challenge in materials science because of the complex relationship between composition and microstructure. In this Research Article, we demonstrate a combinatorial strategy for the exploration of composition dependence of microstructure. This strategy is comprised of alloy library synthesis followed by high-throughput microstructure characterization. As an example, we synthesized a ternary Au-Cu-Si composition library containing over 1000 individual alloys using combinatorial sputtering. We subsequently melted and resolidified the entire library at controlled cooling rates. We used scanning optical microscopy and X-ray diffraction mapping to explore trends in phase formation and microstructural length scale with composition across the library. The integration of combinatorial synthesis with parallelizable analysis methods provides a efficient method for examining vast compositional ranges. The availability of microstructures from this vast composition space not only facilitates design of new alloys by controlling effects of composition on phase selection, phase sequence, length scale, and overall morphology, but also will be instrumental in understanding the complex process of microstructure formation in alloys.
19 citations (Crossref) [2023-10-31] Place: United States Li, Yanglin. Center for Research on Interface Structures and Phenomena, Yale University, New Haven, Connecticut 06511, United States. Li, Yanglin. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut 06511, United States. Jensen, Katharine E. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut 06511, United States. Liu, Yanhui. Center for Research on Interface Structures and Phenomena, Yale University, New Haven, Connecticut 06511, United States. Liu, Yanhui. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut 06511, United States. Liu, Jingbei. Center for Research on Interface Structures and Phenomena, Yale University, New Haven, Connecticut 06511, United States. Liu, Jingbei. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut 06511, United States. Gong, Pan. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut 06511, United States. Scanley, B Ellen. Center for Research on Interface Structures and Phenomena, Yale University, New Haven, Connecticut 06511, United States. Scanley, B Ellen. Department of Physics, Southern Connecticut State University, New Haven, Connecticut 06515, United States. Broadbridge, Christine C. Center for Research on Interface Structures and Phenomena, Yale University, New Haven, Connecticut 06511, United States. Broadbridge, Christine C. Department of Physics, Southern Connecticut State University, New Haven, Connecticut 06515, United States. Schroers, Jan. Center for Research on Interface Structures and Phenomena, Yale University, New Haven, Connecticut 06511, United States. Schroers, Jan. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut 06511, United States.
Keywords: *Alloys/ch [Chemistry]; *Combinatorial Chemistry Techniques/mt [Methods]; *Copper/ch [Chemistry]; *Gold/ch [Chemistry]; *Silicon/ch [Chemistry]; Alloys; Combinatorial Chemistry Techniques; Copper; Gold; High-Throughput Screening Assays; Materials Testing; Physical Phenomena; Silicon; alloy; alloy microstructure; chemistry; combinatorial chemistry; combinatorial materials science; copper; dept.phy; gold; high throughput screening; high-throughput; materials testing; phase mapping; physical phenomena; procedures; silicon

Combinatorial exploration of color in gold-based alloys - Liu, Jingbei; Liu, Yanhui; Gong, Pan; Li, Yanglin; Moore, Kimberly M.; Scanley, Ellen; Walker, Fred; Broadbridge, Christine; Schroers, Jan (Gold Bulletin, 2015)
Combinatorial approaches comprised of combinatorial magnetron co-sputtering deposition and fast screening methods are introduced to study color as a function of composition in Au-based alloys. The microstructures of the thin films and bulk alloys are identified by X-ray diffraction, and their colors of the alloys are characterized by optical reflectivity. The results reveal that when comparing microstructures and reflectivity, thin films are similar to bulk alloys. In Au-Ag-Cu solid solutions, the color of the ternary alloy follows the rule of mixture. For colors resulting from AuAl2 intermetallic, the color of an alloy scales with the percentage of the intermetallic phase and the deviation from its ideal binary composition. In the Au-Al-Cu library, we found a ∼90 % AuAl2 area fraction compositional window where copper addition can be tuned to improve mechanical properties while keeping purple color, even though Al and CuAl2 phases exist. Moreover, when comparing the color in Au-Cu-Si-Ag amorphous and crystalline state solid solution for the same composition, the colors are essentially identical. © 2015 The Author(s).
32 citations (Crossref) [2023-10-31] Citation Key Alias: pop00036 tex.type: [object Object]
Keywords: Aluminum; Amorphous alloys; Amorphous silicon; Amorphousalloys; Binary composition; Color; Combinatorial approach; Crystalline materials; Crystalline state; Decorative thin film coating; Decorative thin films; Gold; Gold alloys; Gold based alloys; Gold coatings; Intermetallic phase; Intermetallics; Magnetron co-sputtering; Magnetrons; Microstructure; Optical reflectivity; Reflection; Silver; Silver alloys; Solid solution; Solid solutions; Thin films; X ray diffraction; dept.phy

Noble metal high entropy alloys - Sohn, Sungwoo; Liu, Yanhui; Liu, Jingbei; Gong, Pan; Prades-Rodel, Silke; Blatter, Andreas; Scanley, B. Ellen; Broadbridge, Christine C.; Schroers, Jan (Scripta Materialia, 2017)
A series of noble metal high entropy alloys with up to six constituent elements has been produced by casting. PtPdRhIrCuNi forms single-phase face-centered cubic solid solution, and its stability is confirmed by annealing experiments. This alloy deforms homogeneously to ~30% to a high ultimate compression strength of 1839MPa. We discuss rules for the formation of single-phase solid solution.
70 citations (Crossref) [2023-10-31]
Keywords: Annealing experiments; Compressive properties; Compressive property; Constituent elements; Entropy; FCC structure; Face-centered cubic; Fcc structures; High entropy alloys; Phase stability; Precious metals; Single phase; Solid solution; Solid solutions; Ultimate compression; dept.phy

Combinatorial screening of Pd-based quaternary electrocatalysts for oxygen reduction reaction in alkaline media - Li, Jinyang; Stein, Helge S.; Sliozberg, Kirill; Liu, Jingbei; Liu, Yanhui; Sertic, Genevieve; Scanley, Ellen; Ludwig, Alfred; Schroers, Jan; Schuhmann, Wolfgang; Taylor, André D. (Journal of Materials Chemistry, 2017)
The implementation of electrochemical systems such as fuel cells has been hindered by the slow development of low cost high activity catalysts. Here we examine the oxygen reduction reaction performance of a combinatorial Pd-Au-Ag-Ti thin film library using high-throughput screening and correlate the electrochemical behavior to the crystallographic properties. We find compositions of ca. 40-60 at% Pd and 30-35 at% Au exhibit both a low overpotential of close to the value of pure Pt as well as high current density. We also observe a volcano-like relationship between the overpotential and the solid formation strain. This study provides compositional guidance towards the future synthesis of nanostructured quaternary Pd-Au-Ag-Ti alloys and suggests the potential for broader application of high-throughput electrochemical characterization by means of an automatic scanning droplet cell. © The Royal Society of Chemistry.
30 citations (Crossref) [2023-10-31] Citation Key Alias: pop00049 tex.type: [object Object]
Keywords: Catalyst activity; Combinatorial screenings; Crystallographic properties; Electrocatalysts; Electrochemical behaviors; Electrochemical characterizations; Electrochemical systems; Electrolytic reduction; Fuel cells; Gold; High current densities; High throughput screening; Oxygen reduction reaction; Reduction; Silver; Silver alloys; Throughput; Titanium alloys; dept.phy

Combinatorial development of antibacterial Zr-Cu-Al-Ag thin film metallic glasses. - Liu, Yanhui; Padmanabhan, Jagannath; Cheung, Bettina; Liu, Jingbei; Chen, Zheng; Scanley, B Ellen; Wesolowski, Donna; Pressley, Mariyah; Broadbridge, Christine C; Altman, Sidney; Schwarz, Udo D; Kyriakides, Themis R; et al. (Scientific Reports, 2016)
Metallic alloys are normally composed of multiple constituent elements in order to achieve integration of a plurality of properties required in technological applications. However, conventional alloy development paradigm, by sequential trial-and-error approach, requires completely unrelated strategies to optimize compositions out of a vast phase space, making alloy development time consuming and labor intensive. Here, we challenge the conventional paradigm by proposing a combinatorial strategy that enables parallel screening of a multitude of alloys. Utilizing a typical metallic glass forming alloy system Zr-Cu-Al-Ag as an example, we demonstrate how glass formation and antibacterial activity, two unrelated properties, can be simultaneously characterized and the optimal composition can be efficiently identified. We found that in the Zr-Cu-Al-Ag alloy system fully glassy phase can be obtained in a wide compositional range by co-sputtering, and antibacterial activity is strongly dependent on alloy compositions. Our results indicate that antibacterial activity is sensitive to Cu and Ag while essentially remains unchanged within a wide range of Zr and Al. The proposed strategy not only facilitates development of high-performing alloys, but also provides a tool to unveil the composition dependence of properties in a highly parallel fashion, which helps the development of new materials by design.
51 citations (Crossref) [2023-10-31] Place: England Liu, Yanhui. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Liu, Yanhui. Department of Mechanical Engineering and Materials Science, Yale University, New Haven CT 06511, USA. Padmanabhan, Jagannath. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Padmanabhan, Jagannath. Department of Biomedical Engineering, Yale University, New Haven CT 06511, USA. Cheung, Bettina. Department of Biomedical Engineering, Yale University, New Haven CT 06511, USA. Liu, Jingbei. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Liu, Jingbei. Department of Mechanical Engineering and Materials Science, Yale University, New Haven CT 06511, USA. Chen, Zheng. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Chen, Zheng. Department of Mechanical Engineering and Materials Science, Yale University, New Haven CT 06511, USA. Scanley, B Ellen. Department of Physics, Southern Connecticut State University, New Haven, Connecticut 06515, USA. Wesolowski, Donna. Department of Molecular, Cellular and Developmental Biology, Yale University, New Haven CT 06520, USA. Pressley, Mariyah. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Broadbridge, Christine C. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Broadbridge, Christine C. Department of Physics, Southern Connecticut State University, New Haven, Connecticut 06515, USA. Altman, Sidney. Department of Molecular, Cellular and Developmental Biology, Yale University, New Haven CT 06520, USA. Schwarz, Udo D. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Schwarz, Udo D. Department of Mechanical Engineering and Materials Science, Yale University, New Haven CT 06511, USA. Schwarz, Udo D. Department of Chemical and Environmental Engineering, Yale University, New Haven CT 06520, USA. Kyriakides, Themis R. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Kyriakides, Themis R. Department of Biomedical Engineering, Yale University, New Haven CT 06511, USA. Kyriakides, Themis R. Department of Pathology, Yale University, New Haven CT 06520, USA. Schroers, Jan. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Schroers, Jan. Department of Mechanical Engineering and Materials Science, Yale University, New Haven CT 06511, USA.
Keywords: *Alloys/ch [Chemistry]; *Aluminum/ch [Chemistry]; *Anti-Bacterial Agents/ch [Chemistry]; *Combinatorial Chemistry Techniques; *Silver/ch [Chemistry]; Alloys; Alloys/pd [Pharmacology]; Aluminum; Anti-Bacterial Agents; Anti-Bacterial Agents/pd [Pharmacology]; Combinatorial Chemistry Techniques; Copper; Copper/ch [Chemistry]; Escherichia coli; Escherichia coli/de [Drug Effects]; Escherichia coli/gd [Growth & Development]; Escherichia coli/ul [Ultrastructure]; Glass; Glass/ch [Chemistry]; Microscopy; Atomic Force; Silver; Structure-Activity Relationship; Zirconium; Zirconium/ch [Chemistry]; alloy; aluminum; antiinfective agent; atomic force microscopy; chemistry; combinatorial chemistry; copper; dept.phy; drug effect; glass; growth; development and aging; peer-reviewed; silver; structure activity relation; ultrastructure; zirconium

Determination of critical cooling rates in metallic glass forming alloy libraries through laser spike annealing. - Bordeenithikasem, Punnathat; Liu, Jingbei; Kube, Sebastian A; Li, Yanglin; Ma, Tianxing; Scanley, B Ellen; Broadbridge, Christine C; Vlassak, Joost J; Singer, Jonathan P; Schroers, Jan (Scientific reports, 2017)
The glass forming ability (GFA) of metallic glasses (MGs) is quantified by the critical cooling rate (R C). Despite its key role in MG research, experimental challenges have limited measured R C to a minute fraction of known glass formers. We present a combinatorial approach to directly measure R C for large compositional ranges. This is realized through the use of compositionally-graded alloy libraries, which were photo-thermally heated by scanning laser spike annealing of an absorbing layer, then melted and cooled at various rates. Coupled with X-ray diffraction mapping, GFA is determined from direct R C measurements. We exemplify this technique for the Au-Cu-Si system, where we identify Au56Cu27Si17 as the alloy with the highest GFA. In general, this method enables measurements of R C over large compositional areas, which is powerful for materials discovery and, when correlating with chemistry and other properties, for a deeper understanding of MG formation.
44 citations (Crossref) [2023-10-31] Place: England Bordeenithikasem, Punnathat. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Liu, Jingbei. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Kube, Sebastian A. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Li, Yanglin. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Ma, Tianxing. Department of Mechanical and Aerospace Engineering, Rutgers University, Piscataway, New Jersey, 08854, USA. Scanley, B Ellen. Department of Physics, Southern Connecticut State University, New Haven, Connecticut, 06515, USA. Broadbridge, Christine C. Department of Physics, Southern Connecticut State University, New Haven, Connecticut, 06515, USA. Vlassak, Joost J. School of Engineering and Applied Science, Harvard University, Cambridge, Massachusetts, 02138, USA. Singer, Jonathan P. Department of Mechanical and Aerospace Engineering, Rutgers University, Piscataway, New Jersey, 08854, USA. Schroers, Jan. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. jan.schroers@yale.edu. Erratum in (EIN)
Keywords: dept.phy; peer-reviewed